Changes in ichthyofauna composition along a gradient from clearwaters to blackwaters in coastal streams of Atlantic forest (southeastern Brazil) in relation to environmental variables - Gonçalves, Cristina da Silva [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Sociedade Brasileira de Ictiologia, 2012)
A falta de conhecimento dos peixes de água doce em riachos costeiros no estado de São Paulo é preocupante, considerando que estes riachos estão inseridos em um bioma brasileiro extremamente ameaçado, a floresta Atlântica. O objetivo deste trabalho é investigar a composição da ictiofauna de riachos de águas claras e pretas em uma área preservada da Mata Atlântica. A pesca elétrica foi utilizada para amostrar a ictiofauna. Foram coletadas 20 espécies, sendo Astyanax ribeirae, Mimagoniates microlepis e Hollandichthys multifasciatus (Characiformes, Characidae), as mais representativas. de modo geral, o padrão de ocorrência e distribuição da ictiofauna observado variou de acordo com as características dos habitats, tanto no gradiente longitudinal nos riachos de águas claras, quanto entre os riachos de águas claras e o de águas pretas. Nos riachos de águas claras, os trechos de cabeceiras apresentaram riqueza e diversidade de espécies menor, enquanto o inverso ocorreu nos pontos médios e inferiores. Estas variações longitudinais da ictiofauna provavelmente estão associadas às características dos ambientes (profundidade, correnteza e substrato) em que foram encontradas, visto que a diversidade de habitats foi maior nos trechos de cabeceiras e menor nos trechos médios e inferiores. As variáveis físicas e químicas da água parecem não ter influenciado tanto a distribuição das espécies nos riachos de águas claras, porém as diferenças na composição da ictiofauna entre riachos de águas claras e de águas pretas foram influenciadas principalmente pelo pH. Ao contrário das diferenças espaciais, não foram registradas diferenças temporais nas ictiocenoses, provavelmente devido à ausência de um período seco pronunciado na região de estudo

The lack of knowledge of the freshwater ichthyofauna of coastal streams in the State of São Paulo (Brazil) is a cause of concern, as these streams are inserted in the Atlantic forest, a hotspot highly threatened. The aim of the present study is to investigate the freshwater ichthyofauna composition of clear and blackwater streams in a preservation area of Brazilian Atlantic forest. Fish samples were taken using electrofishing. A total of 20 species were registered, with Astyanax ribeirae, Hollandichthys multifasciatus, and Mimagoniates microlepis (Characiformes, Characidae) as the more representative. In general, the observed pattern of occurrence and distribution of fish species varied according to habitat characteristics, due to the longitudinal gradient in clearwaters, and among clearwaters and blackwaters. In clearwater streams, the headwater stretches had lower species diversity, while the opposite occurred in the middle and lower sites. These longitudinal variations of ichthyofauna were related with habitat characteristics (depth, stream flow, and bottom type) in which they were found, since the diversity of habitats was higher in headwaters and lower in downstream reaches (middle and lower sites). The physical and chemical variables of water do not seem to have influenced the distribution of species in clearwater streams, but the clear and blackwater fish composition was influenced mainly by pH concentration. Unlike the spatial differences, significant temporal differences were not registered in fish assemblages, probably due to the absence of a pronounced dry season in the studied region.
Keywords: Fish structure; Habitat diversity; Jureia-Itatins; pH concentration